Failure signals in sustainable crowdfunding: distinct reactions driven by crowd investors' experience - Eva Alexandra Jakob; Jeannette Mai Dinh; Marius Claus Wehner (Small Business Economics, 2025)
A significant number of crowdfunding campaigns, including sustainable campaigns, fail after securing successful funding. Although failure implies investment losses for crowd investors and potentially impacts investors' future investment behavior, our understanding of how crowd investors respond to failures remains limited. This study proposes that prior crowdfunding experience explains important differences in how~crowd investors~react~to failure signals. Drawing on signaling theory, we argue that prior crowdfunding experience results in less adverse reactions to failure signals. Moreover, we propose that crowdfunding experiences explain differences in the reactions to failure signals of sustainable campaigns. Two vignette-based experiments (studies 1 and 2) reveal that experienced investors react less negatively to investment failures than those without this experience. Further, our studies show a reverse effect for sustainable campaigns, suggesting that experienced crowd investors tend to be less forgiving of failures in environmental campaigns than commercial ones, compared to inexperienced crowd investors. An additional empirical survey indicates that a possible explanation for the differences between crowd investors' reactions may be found in the specific personal values of crowd investors. We contribute to entrepreneurial finance and crowdfunding literature by showing how experienced crowd investors interpret conflicting signals—failure and sustainability—emphasizing the role of investor characteristics in shaping signal effectiveness.
Keywords: L26; A13; G23; M13; Q01; 330; Crowd investor; Experience; Failure; Investment behavior; Sustainable ventures